A Novel Approach to Construct Deterministic Finite State Automata (International Journal of Engineering and Computer Science, 2014)
The finite-state automaton is one of the most significant tools of computational linguistics. It is divided into two parts Deterministic and Nondeterministic. In this paper description of how automata are used to describe regular languages is given. Some illustrations about finite state automaton and state-transition table and their contribution to represent regular languages are given in this paper.  An algorithm to construct deterministic finite state automata is presented. This algorithm gives finite state automaton of a word over regular languages instantly.